Implementasi Klasifikasi Datamining dengan Algoritma C4.5 untuk Rekomendasi Pemilihan Fakultas Perguruan Tinggi Berdasarkan Minat dan Bakat Siswa SMK - Senna Hendrian; V.H Valentino; Wisdariah, Wisdariah; Riezca Talita Trista; Dudi Parulian (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
Selecting a faculty that aligns with students’ interests and talents is a strategic step in determining the success of higher education and future career paths. However, most vocational high school (SMK) students still face difficulties in identifying the most suitable faculty due to the lack of data-driven analysis. This study implements the C4.5 classification algorithm within data mining techniques to build an automatic and measurable faculty recommendation system. The dataset consists of attributes such as SMK major, interest level, aptitude test results, academic grade average, and gender, with the output being the recommended faculty. The C4.5 algorithm was chosen for its ability to generate a transparent and interpretable decision tree, which helps both guidance counselors and students understand the rationale behind the recommendations. The experimental results show that the constructed classification model achieved an accuracy rate of 88%, based on cross-validation testing using data from 12th-grade students. The implementation of this system is expected to serve as an objective tool in the faculty selection process and to promote a data-driven decision-making approach in secondary education environments.